Does Learning Motivation Essential? Examining Readiness on Self-Directed Learning and Technology Towards Cognitive Presence - Jeffri Ardiyanto; Oktia Woro Kasmini Handayani; Tri Joko Raharjo; RR Sri Endang Pujiastuti (International Conference on Science, Education, and Technology, 2021)
Nowadays, technology is rapidly developed, which affects various aspects, including education. Technology development increase learning motivation; therefore, student motivation determines learning achievement. Technology, besides improve student understanding, it is providing engaging learning activities. Previous research has not explored student learning readiness to learning motivation; moreover, technology dynamics in the learning process are constantly evolving. The study examines the effect of learning motivation in mediating self-directed learning readiness and technology readiness on cognitive presence. This study uses a quantitative approach involving 167 students as respondents who employ a learning management system during lectures. The research distributed an online questionnaire to obtain data and analyzed using SEM AMOS. The results show that self-directed learning readiness influences motivation and cognitive presence; it means learning motivation partially mediates. This study also proves that technology readiness directly affects learning motivation and cognitive presence; learning motivation partially mediates. This study indicates self-directed learning readiness and technology readiness shape learning motivation. This research proves readiness to learn and ready-to-use technology raise learning motivation. Students are motivated to increase their understanding through technology. The research result is beneficial for understanding the urge of learning motivation to exaggerate students' cognitive aspects.